(untitled) (International Journal of Engineering and Computer Science, 2024)
Cloud computing has revolutionized business operations by providing scalable, on-demand access to computing resources. This paper examines the impact of cloud computing on modern enterprises, focusing on its benefits, challenges, and future trends. Through a review of existing literature and case studies, we analyse how cloud computing enhances operational efficiency, enables innovation, and introduces security and privacy concerns. The findings highlight the need for strategic implementation to fully leverage cloud technologies.